2017
DOI: 10.1158/1538-7445.am2017-ct074
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT074: Non-comparative, open-label, multiple cohort, phase 1/2 study to evaluate nivolumab (NIVO) in patients with virus-associated tumors (CheckMate 358): Efficacy and safety in Merkel cell carcinoma (MCC)

Abstract: Background: NIVO (anti-PD-1) is approved for the treatment of several cancers including advanced melanoma, but its efficacy in other types of skin cancer has not yet been evaluated. MCC is a rare and aggressive form of skin cancer, with most tumors being associated with the Merkel cell polyomavirus. MCCs frequently express PD-L1, and MCC-reactive T cells express PD-1. Methods: In CheckMate 358 (NCT02488759), patients (pts) with 5 types of advanced virus-associated cancers who had received ≤2 pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 0 publications
5
112
0
14
Order By: Relevance
“…Only around half of patients with advanced-stage MCC respond to immune-checkpoint blockade 104,136,137 . Moreover, even during the very short follow-up period of the reported immunotherapy trials, a substantial number of patients developed acquired resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only around half of patients with advanced-stage MCC respond to immune-checkpoint blockade 104,136,137 . Moreover, even during the very short follow-up period of the reported immunotherapy trials, a substantial number of patients developed acquired resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, three phase II open-label clinical trials of therapeutic antibodies against PD1 or PDL1 have demonstrated high and durable response rates 104,136,137 (TABLE 2) that are more durable than those reported in historical data of patients treated with chemotherapy. In the first study to report immune-checkpoint blockade using the anti-PD1 antibody pembrolizumab in patients with advanced-stage MCC, the response rate was 56% 136 .…”
Section: Managementmentioning
confidence: 99%
“…Nivolumab, another humanized IgG4 antibody against PD‐1, has demonstrated similar results to pembrolizumab, with an ORR of 68%, and 87% of participants maintaining their response at 6‐month follow‐up . A phase I/II trial of nivolumab combination therapies in virus‐associated tumors is ongoing (NCT02488759).…”
Section: Discussionmentioning
confidence: 97%
“…Immune checkpoint inhibitors are another treatment option for MCC. Two monoclonal antibodies against programmed cell death 1 have been investigated as first‐line treatments for patients with advanced MCC, including nivolumab for patients with stage II–IV MCC and pembrolizumab for patients with stage IIIB–IV MCC . First‐ and second‐line avelumab treatments have demonstrated great efficacy in patients with stage IV metastatic MCC .…”
Section: Discussionmentioning
confidence: 99%